Basic Gynecologic Ultrasound Examination (Level I): DEGUM, ÖGUM, and SGUM Recommendations - Grab, Dieter; Merz, Eberhard; Eichhorn, Karl-Heinz; Tutschek, Boris; Kagan, Karl Oliver; Heling, Kai-Sven; Faber, Renaldo; Klaritsch, Philipp; Rempen, Andreas; Kähler, Christiane; Henrich, Wolfgang; Manegold-Brauer, Gwendolin; Helmy, Samir; Hoopmann, Markus (Ultraschall in der Medizin - European Journal of Ultrasound, 2022)
Ultrasound has become an essential diagnostic tool in gynecology, and every practicing gynecologist must be able to differentiate normal from pathologic findings, such as benign or malignant pelvic masses, adnexal torsion, pelvic inflammation disease, endometriosis, ectopic pregnancies, and congenital uterine malformations at least on a basic level. A standardized approach to the correct settings of the ultrasound system, the indications for gynecologic ultrasound investigations, and the sonographic appearance of normal anatomy and common pathologic findings in the standard planes are important prerequisites for safe and confident clinical management of gynecologic patients. Based on current publications and different national and international guidelines, updated DEGUM, ÖGUM, and SGUM recommendations for the performance of basic gynecologic ultrasound examinations were established.Die sonografische Basisuntersuchung in der Gynäkologie umfasst Diagnostik und Differenzialdiagnostik in der täglichen Praxis: Gesundheitsvorsorge, Abgrenzung der Normalbefunde von pathologischen Befunden wie kongenitale Fehlbildungen, benigne und maligne Tumoren, Adnextorsionen, entzündliche Erkrankungen des inneren Genitals, Endometriose, gestörte Frühgraviditäten und Tubargraviditäten sowie Fragestellungen zu Kontrazeption und Fertilität. Die Standardisierung der Untersuchungstechnik sowie die genaue Definition der Leistungsinhalte für die Basisdiagnostik und für die weiterführende Diagnostik (DEGUM-Stufe II) analog des schon seit Jahren in der pränatalen Diagnostik bewährten Mehrstufenkonzepts der DEGUM sind inzwischen auch in die gynäkologische Sonografie implementiert worden. Als Grundlage für eine strukturierte Aus- und Weiterbildung im Rahmen dieses Stufenkonzepts haben DEGUM, ÖGUM und SGUM die Qualitätsanforderungen und die Leistungsinhalte für gynäkologische sonografische Basisuntersuchungen (DEGUM-Stufe I) entsprechend dem gegenwärtigen Kenntnisstand sowie anhand nationaler und internationaler Standards und Empfehlungen aktualisiert.
Keywords: gynecology; education; training; quality Assurance; basic ultrasound